2021
DOI: 10.1093/jxb/erab183
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-like cytoplasmic kinase MAZZA mediates developmental processes with CLAVATA1 family receptors in Arabidopsis

Abstract: The receptor-like kinases (RLKs) CLAVATA1 (CLV1) and BARELY ANY MERISTEMs (BAM1–BAM3) form the CLV1 family (CLV1f), which perceives peptides of the CLV3/EMBRYO SURROUNDING REGION (ESR)-related (CLE) family within various signaling pathways of Arabidopsis thaliana. CLE peptide signaling, which is required for meristem size control, vascular development, and pathogen responses, involves the formation of receptor complexes at the plasma membrane. These complexes comprise RLKs and co-receptors in varying compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…To gain insights into how CLV1 and BAM1 may impact the lateral root formation, we investigated the cell‐type expression pattern of CLV1‐GFP and BAM1‐GFP proteins during LRP development. Confocal microscopy analysis showed that CLV1‐GFP fusion protein was indeed localized to the phloem companion cells in the basal regions of LRP and emerged lateral root (Figure 5e), consistent with the literature (Araya et al., 2014; Blümke et al., 2021). In addition, CLV1‐GFP signal was also observed in the companion cells adjacent to LRP and emerged lateral root (Figure S5d).…”
Section: Resultssupporting
confidence: 90%
“…To gain insights into how CLV1 and BAM1 may impact the lateral root formation, we investigated the cell‐type expression pattern of CLV1‐GFP and BAM1‐GFP proteins during LRP development. Confocal microscopy analysis showed that CLV1‐GFP fusion protein was indeed localized to the phloem companion cells in the basal regions of LRP and emerged lateral root (Figure 5e), consistent with the literature (Araya et al., 2014; Blümke et al., 2021). In addition, CLV1‐GFP signal was also observed in the companion cells adjacent to LRP and emerged lateral root (Figure S5d).…”
Section: Resultssupporting
confidence: 90%
“…In vitro bioassays comparing root growth in the presence or absence of exogenous peptide ligands provide an easy readout and are widely employed to evaluate how plants respond to peptide-dependent signaling (Anne et al , 2018; Blumke et al , 2021; Breda et al , 2019; Graeff et al , 2020; Hazak et al , 2017; Hu et al , 2018; Poncini et al , 2017). To correlate peptide-dependent receptor signalling with CME capacity, we selected several classes of peptide ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Agrobacterium culture preparation and tobacco leaf infiltration were performed as described (Sosso et al ., 2015). As a control, pAB118:AtMAZZA:mCherry carrying the coding sequence of Arabidopsis MAZZA gene fused at the C‐terminus with mCherry driven by the β‐estradiol inducible CaMV 35S promoter was used (Blümke et al ., 2021). Fluorescence was detected on an Olympus SpinSR (Olympus Corp., Hamburg, Germany) with excitation/emission 488/522–572 nm (eGFP) and 561/667–773 nm (chlorophyll).…”
Section: Methodsmentioning
confidence: 99%